2016
DOI: 10.1093/mnras/stw2812
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the rotational properties of multiple stellar populations in M13: a faster rotation for the ‘extreme’ chemical subpopulation

Abstract: We use radial velocities from spectra of giants obtained with the WIYN telescope, coupled with existing chemical abundance measurements of Na and O for the same stars, to probe the presence of kinematic differences among the multiple populations of the globular cluster (GC) M13. To characterise the kinematics of various chemical subsamples, we introduce a method using Bayesian inference along with an MCMC algorithm to fit a six-parameter kinematic model (including rotation) to these subsamples. We find that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
66
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 109 publications
13
66
2
2
Order By: Relevance
“…Our findings are remarkably similar to those of Cordero et al (2017), who found the extreme population of the cluster NGC 6205 to be rotating faster than the remaining populations. Similar to NGC 6093, an advanced dynamical state has also been suggested for NGC 6205 (see Savino et al 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are remarkably similar to those of Cordero et al (2017), who found the extreme population of the cluster NGC 6205 to be rotating faster than the remaining populations. Similar to NGC 6093, an advanced dynamical state has also been suggested for NGC 6205 (see Savino et al 2018).…”
Section: Discussionsupporting
confidence: 90%
“…While no differences were found in 47 Tuc (Milone et al 2018), NGC 6362 (Dalessandro et al 2018b), or NGC 6352 (Libralato et al 2019), Bellini et al (2018) found rotational differences among the populations of the complex cluster ω Cen, in the sense that main sequence stars with enhanced helium and iron abundances rotate slower. On the other hand, Cordero et al (2017) reported enhanced rotation for the extremely N-enriched population in NGC 6205 (M13). Surprisingly, NGC 6205 also appears to be in a late dynamical stage, given that Savino et al (2018) found the populations are almost completely mixed 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Richer et al (2013), Bellini et al (2015), and Bellini et al (2018), using HST proper-motion measurements for, respectively, 47 Tucanae and NGC2808, and Milone et al (2018), using Gaia proper-motion measurements of 47 Tuc, have shown that secondgeneration (2G) stars (defined as those with enhancements in the abundances of elements such as Na, N, and He) are characterized by a more radially anisotropic velocity dispersion than first-generation (1G) stars. 1 Cordero et al (2017) studied the rotational properties of the multiple populations of M13 and found that the extreme 2G population rotates more rapidly than the intermediate 2G. In M5, Lee (2017) found that 2G stars are characterized by a significant rotation while 1G stars show no rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, deviations from the sharply truncated King phase space distribution (e.g., see the cases of NGC 1851, as studied by Olszewski et al 2009;Marino et al 2014, NGC 5694 by Correnti et al 2011;Bellazzini et al 2015, and several others, as discussed, e.g., by Carballo-Bello et al 2018), spherical symmetry (e.g., Chen & Chen 2010), and pressure isotropy (e.g., van de Ven et al 2006;Bellini et al 2014Bellini et al , 2017Watkins et al 2015) are found in a growing number of GGCs. Also the observational evidence of systemic rotation is increasing (e.g., Anderson & King 2003;Lane et al 2009Lane et al , 2010Bellazzini et al 2012;Bianchini et al 2013;Fabricius et al 2014;Kacharov et al 2014;Kimmig et al 2015;Lardo et al 2015;Bellini et al 2017;Boberg et al 2017;Cordero et al 2017;Ferraro et al 2018b;Kamann et al 2018), possibly suggesting that, when properly surveyed, the majority of GCs rotate at some level. In particular, Ferraro et al (2018b) investigated the intermediate/external region of 11 clusters, demonstrating the presence of internal rotation in almost all of them.…”
Section: Introductionmentioning
confidence: 99%